EVALUASI KERJA SAMA TIONGKOK – MYANMAR DALAM MENANGANI PERDAGANGAN PEREMPUAN PADA 2008 – 2013 - Widowati, Arie; Susitianingsih, Hermini; Wahyudi, Fendy Eko (Journal of International Relations, 2016)
Women trafficking is one of international crimes which keeps increasing by thenumber of the cases and also the victims. One of the examples is trafficking inwomen that happens in China and Myanmar. In order to tackle the crime, bothcountries enacted a cooperation in 2007, considering that the crime takesplace across both national borders. Thus the purpose of this research is to givean explanation regarding this phenomenon over the period 2008 – 2013. Inorder to identify the linkage between the two variables, Kenneth Waltz’s theoryof international cooperation is applied as well as the concept of security whichencompasses ‘high politics’ and ‘low politics’ (Kenneth Waltz and Ripsman).This research results in a conclusion that the increase of trafficking in womencases during that period was due to lack of efforts and implementation ofcooperation which were of both countries. Moreover, the issue of trafficking inwomen being put into the ‘low politics’ sector instead of ‘high politics’ resultedin low urgency which also affected this phenomenon.